Transstadial metabolic priming mediated by larval nutrition in female Aedes albopictus mosquitoes. (May 2020) - Dittmer, Jessica; Gabrieli, Paolo
Graphical abstract: Highlights: Larval nutrient deprivation can be compensated by increased development time. Nutrient-poor larval conditions had a priming effect on adult female metabolism. Females from poor larval habitats accumulated lower nutrient stores from sucrose. Females from poor larval habitats survived longer with access to sugar. Larval nutrition affects adult female metabolism and may impact vectorial capacity. Abstract: Mosquitoes are important vectors of human pathogens, which are transmitted by female mosquitoes via blood-feeding. Larval nutrition can have an important impact on the number of blood meals taken by adult females shortly after emergence, as nutritional deficiencies during the larval stage may result in pre-vitellogenic blood meals, which are not invested into egg development but into the endogenous nutrient reserves of the female. Here, we investigated the impact of nutrient deprivation during the larval stage on adult nutrient metabolism, longevity and blood-seeking behaviour in females of the invasive Asian tiger mosquito Aedes albopictus . We demonstrate that Ae. albopictus females are able to compensate for nutrient deprivation during the larval stage by increasing their development time until sufficient nutrients are acquired. Nonetheless, nutrient-poor larval conditions had a long-lasting priming effect on adult female metabolism, since these females accumulated lower nutrient reserves from carbohydrates and survived longer compared to females reared in nutrient-rich larval conditions. Moreover, nutrient and ATP levels of females from nutrient-poor larval conditions remained stable over a longer timespan without access to additional carbohydrates. This suggests differences in adult female metabolism in response to larval nutrition, with potential impact on the vectorial capacity of female mosquitoes.